Incorporación del Software MATLAB en el Aprendizaje de “Sistemas de Ecuaciones Lineales” para el Décimo Año de Educación General Básica. - Romero Bonifaz, Verónica Alejandra (2022)
In today's society where virtual education forces teachers to present their subjects in an attractive way, the selection of didactic resources must be based on their objective quality and on the way in which their specific characteristics match the curricular aspects of the educational context to be achieved. Teachers need to be innovative and seek to continuously improve by using new alternatives within the dynamics of their daily practice. For this reason, the present research work had the objective of incorporating the mathematical software MATLAB in the learning of "Systems of Linear Equations" for the Tenth Year of General Basic Education. The research had a non-experimental design of descriptive type, the data collection was online through a survey conducted with the Google Forms tool. The data obtained were processed with the Microsoft Excel computer package using Descriptive Statistics techniques. The results obtained allow us to conclude that traditional education does not guarantee significant learning, so the proposal to implement ICTs in the teaching-learning process is vitally important, specifically the use of educational software such as MATLAB. This will encourage autonomous learning in solving exercises for systems of linear equations with an effective tool for educational development in today's knowledge society.